The Effect of Certification Learning Model and Principle’s Leadership Style on Teachers’ Work Motivation - M. Yusuf Alfian Rendra Anggoro KR; Uli Wildan Nuryanto; Hilarius Wandan; Roy Setiawan; Toto Heru Dwi Handoko (Journal on Education, 2023)
In order to help instructors complete their work in accordance with the required standards and help the school reach its objectives, work motivation plays a significant role. The goal of this study is to evaluate and analyze how the teacher certification model and the principal's leadership style affect the work motivation of teachers. Ex-Post Facto research with a 3x2 level design is what this study is. SEM measuring method and two-way ANOVA were utilized for data gathering. The findings showed that instrument created using the measurement model is valid and consistently measures teacher work motivation with a value of construct realibility (CR = 0.90; VE = 0.58); principal leadership style has an impact on teacher work motivation; the teacher certification model has an impact on teacher work motivation; there is a relationship between the principle leadership style and the teacher certification model, and leadership style, the teacher certification model, and the interaction between the principal leadership style and the teacher certification model all have an impact on the work motivation of teachers. The study's findings suggest that the teacher certification scheme and the principal's leadership style might both influence teachers' levels of motivation at work.